Long-Term Follow-Up of Patients Suffering from Obsessive-Compulsive Disorder Treated as In-Patients - P. C. H. Ashworth; K. M. Davidson; C. M. Shapiro (Behavioural Neurology)
Few patients with obsessive-compulsive disorder (OCD) require in-patient treatment. There is sparse information on outcome of OCD patients treated as in-patients. This paper is a descriptive account of the current functioning of 54 OCD patients treated in hospital, on average 10 years prior to the study. Follow-up reveals that outcome for the majority of patients is poor with 29 (59%) of the sample showing at least mild symptomatology or some difficulty in several areas of functioning.